2011
DOI: 10.1523/jneurosci.5727-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Many Faces of Expertise: Fusiform Face Area in Chess Experts and Novices

Abstract: The fusiform face area (FFA) is involved in face perception to such an extent that some claim it is a brain module for faces exclusively. The other possibility is that FFA is modulated by experience in individuation in any visual domain, not only faces. Here we test this latter FFA expertise hypothesis using the game of chess as a domain of investigation. We exploited the characteristic of chess, which features multiple objects forming meaningful spatial relations. In three experiments, we show that FFA activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
132
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(147 citation statements)
references
References 62 publications
12
132
3
Order By: Relevance
“…Current results hold strong evidence that FFA activation is correlated with domain-specific expertise in naturalistic settings (Bilalić et al, 2011b). Additionally, it is shown that expertise in object-recognition tasks modulates activation in different areas of the brain (Bilalić et al, 2011a), including homologous right-left hemispheric activation in both object and pattern recognition expertise (Bilalić et al, 2010, 2012).…”
Section: Cell Assemblies and The Sparse Distributed Memory Modelsupporting
confidence: 66%
“…Current results hold strong evidence that FFA activation is correlated with domain-specific expertise in naturalistic settings (Bilalić et al, 2011b). Additionally, it is shown that expertise in object-recognition tasks modulates activation in different areas of the brain (Bilalić et al, 2011a), including homologous right-left hemispheric activation in both object and pattern recognition expertise (Bilalić et al, 2010, 2012).…”
Section: Cell Assemblies and The Sparse Distributed Memory Modelsupporting
confidence: 66%
“…Over time, as with car recognition (McGugin et al, 2012) or chess expertise (Bilalić et al, 2011), the expert baseball players’ fusiform gyri may have become selective to differentiate baseball pitch-like objects. Thus, when performing a task that was meant to be a simulation of baseball pitches, the experts’ fusiform areas were more activated than the novices.…”
Section: Discussionmentioning
confidence: 99%
“…Bar hypothesizes that the associations driven in part by the orbitofrontal cortex combine with the visual expertise driven in part by the FFA to produce superior prediction capabilities in visual experts. The fusiform gyrus (FG), an area that includes the FFA, is best know for its face selectivity (Grill-Spector et al, 2004; Kanwisher et al, 1997; Liu et al, 2010), though more recently, studies have shown that the FFA responds to dynamic biological motion (Peelen et al, 2006; Sokolov et al, 2012) and non-face objects, if those objects are associated with expertise (Bilalić et al, 2011; Bilalic et al, 2012; Gauthier et al, 1999; McGugin et al, 2012; Rossion et al, 2004; Tong et al, 2008; Xu, 2005) suggesting a role for FFA, and potentially OFC, in perception-action coupling for expertise-driven rapid visual decisions.…”
Section: Introductionmentioning
confidence: 99%
“…It should be easier to add obscure nomenclature to increase the difficulty of tests for experts, but there is always a concern that below a certain minimal level of expertise, poor performers simply get lumped into an undifferentiated “novice” group. Research in some domains of expertise (e.g., chess) simply do not have reliable measures below a certain skill level (Bilalic, Langner, Erb, & Grodd, 2010; Bilalic, Langner, Ulrich, & Grodd, 2011). In keeping with these goals, we mainly focused on testing subjects from the “normal” population (an undergraduate subject pool and a sample of workers from Amazon Mechanical Turk with US IP addresses), but in Experiment 2 we also test an expert population for one category.…”
Section: Introductionmentioning
confidence: 99%